The heart in congenital diaphragmatic hernia: Knowns, unknowns, and future priorities - Patel, Neil; Massolo, Anna C.; Kraemer, Ulrike S.; Kipfmueller, Florian (Frontiers in Pediatrics, 2022)
There is growing recognition that the heart is a key contributor to the pathophysiology of congenital diaphragmatic hernia, in conjunction with developmental abnormalities of the lung and pulmonary vasculature. Investigations to date have demonstrated altered fetal cardiac morphology, notably relative hypoplasia of the fetal left heart, as well as early postnatal right and left ventricular dysfunction which appears to be independently associated with adverse outcomes. However many more unknowns remain, not least an understanding of the genetic and cellular basis for cardiac dysplasia and dysfunction in CDH, the relationship between fetal, postnatal and long-term cardiac function, and the impact on other parts of the body especially the developing brain. Consensus on how to measure and classify cardiac function and pulmonary hypertension in CDH is also required, potentially using both non-invasive imaging and biomarkers. This may allow routine assessment of the relative contribution of cardiac dysfunction to individual patient pathophysiological phenotype and enable better, individualised therapeutic strategies incorporating targeted use of fetal therapies, cardiac pharmacotherapies, and ECMO. Collaborative, multi-model approaches are now required to explore these unknowns and fully appreciate the role of the heart in CDH.